1991
DOI: 10.2130/jjesp.30.249
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Study on Determinants of Reward Allocation Behaviors

Abstract: The purpose of the present study was to examine determinants of the reward

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Therefore, the subjects in the equity and in the equality condition rated the fairness of allocation of the reward in each of the 60 sentences. The 60 sentences in the questionnaire were collected by Tanaka (1988 Optimal solutions were obtained for equity condition when the number of factors specified was three. For equality condition, the optimal solutions were obtained when the number of factors was specified for two.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the subjects in the equity and in the equality condition rated the fairness of allocation of the reward in each of the 60 sentences. The 60 sentences in the questionnaire were collected by Tanaka (1988 Optimal solutions were obtained for equity condition when the number of factors specified was three. For equality condition, the optimal solutions were obtained when the number of factors was specified for two.…”
Section: Methodsmentioning
confidence: 99%
“…(b) Many factors influence a particular system of allocation, i.e., whether a reward is allocated on the basis of contribution or on the basis of need, or simply equally. Tanaka (1988) has summarized the studies to date, and divided them into two categories.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, numerous studies conducted in both field and laboratory settings indicate that equitable reward allocation—delivering large rewards to good performers and small rewards to poor performers—often facilitates task performance (Collins & Guetzkow, 1964; Lawler, 1971; Porter & Lawler, 1968). Thus, an allocator may distribute rewards equitably because of a belief that such an allocation policy is a means of maximizing performance (Tanaka, 1991).…”
Section: Purpose Of the Reward Allocationmentioning
confidence: 99%
“…Several theorists have suggested that reward allocations may vary with the situation: One allocation principle may be given more weight in one situation, whereas a different principle may be given more weight in another situation (cf. reviews in Bierhoff, Cohen, & Greenberg, 1986;Deutsch, 1985;Greenberg & Cohen, 1982;Messick & Cook, 1983; see also Sigelman &Waitzman, 1991, andTanaka, 1991). In particular, Deutsch (1975Deutsch ( , 1985 has suggested that if productivity or performance is a major concern, reward allocations based on the equity principle are more likely, whereas allocations based on the equality principle are more likely if the concern is with maintaining group harmony and minimizing conflict.…”
mentioning
confidence: 99%